Systematic Review: Nutritional Needs of the Elderly in Indonesia - Evi Sulastri; Rachmat Faisal Syamsu; Aryanti R. Bamahry (PSPP JOURNALS, 2026)
This study aims to analyze the nutritional needs and nutritional status of the elderly in Indonesia through a systematic review approach. Literature was obtained from Google Scholar, Sinta, Scopus, PubMed, and NCBI databases published in the period 2020–2026. The results show that the elderly experience various nutritional problems, ranging from malnutrition to overweight and obesity. The nutritional status of the elderly is influenced by various interrelated factors, such as diet, chronic diseases, physical activity, lifestyle, and family support. Adequate intake of protein, fiber, vitamins, and minerals plays a crucial role in maintaining physical function, preventing degenerative diseases, and improving the quality of life of the elderly. Interventions such as nutrition education, implementing a healthy lifestyle, and utilizing local foods have been shown to have a positive impact on improving the nutritional status of the elderly. Family support also contributes to maintaining regular eating patterns and meeting nutritional needs. This study concludes that optimal nutritional management and early nutritional screening are important strategies to improve the health and quality of life of the elderly in Indonesia.